1999
DOI: 10.1038/sj/leu/2401415
|View full text |Cite
|
Sign up to set email alerts
|

True

Abstract: The Jak/Stat signaling pathway transmits signals from many cytokine and growth factor receptors to target genes in the nucleus. Constitutive activation of Stat3 has recently been observed in many tumor cells and dysregulation of the Stat signaling pathway has been proposed to be implicated in malignant transformation. In a previous study, we found constitutively tyrosine phosphorylated Stat3 in mycosis fungoides tumor cells. Here, we show that the Jak kinase inhibitor, Ag490, inhibits the constitutive binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…Constitutively active STAT3 plays critical roles in the induction of resistance to apoptosis,9 probably by increasing the expression of cyclin D1 and Bcl-2 32,33. AA-PMe-induced suppression of cell proliferation and cell cycle arrest at the G0/G1 phase were closely associated with the downregulation of cyclin D1 expression, which was consistent with the requirement of cyclin D1 for cell cycle transition from G1 to S phase.…”
Section: Discussionsupporting
confidence: 70%
“…Constitutively active STAT3 plays critical roles in the induction of resistance to apoptosis,9 probably by increasing the expression of cyclin D1 and Bcl-2 32,33. AA-PMe-induced suppression of cell proliferation and cell cycle arrest at the G0/G1 phase were closely associated with the downregulation of cyclin D1 expression, which was consistent with the requirement of cyclin D1 for cell cycle transition from G1 to S phase.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have confirmed that STAT3 alterations affect Bcl-2 and Bax protein expression (decreased Bcl-2 and increased Bax) and induce inflammation and apoptosis in many types of tumor cells (6668). Lee et al (69) demonstrated that co-activated NF-κB and STAT3 modulate Bax/Bcl-xL expression and promote cell survival in head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 79%
“…In mycosis fungoides tumor cells, some apoptosis-related genes, such as Bcl-2 and Bax, have been identified as STAT3 target genes (66). In primary cortical neurons and murine models of stroke, the activation of the Jak2/Stat3 pathway by secretoneurin has been found to exert neuroprotective effects and induce neuronal plasticity after hypoxia and ischemic insult (70).…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive STAT3 activation has been known to induce resistance to apoptosis [48], possibly through up-regulation of Bcl-2, Bcl-xl, IAP1/2, and Survivin expression [49]. The down-regulation of Cyclin D1 expression by BSN associated with the suppression in proliferation and accumulation of cells in the sub-G1 phase of the cell cycle, suggesting that Cyclin D1 plays an important role in the observed anti-proliferative effect of BSN.…”
Section: Discussionmentioning
confidence: 99%